Expression of Isl1 during mouse development - Zhuang, Shaowei (2013)
The LIM-homeodomain transcription factor Isl1 plays essential roles in cell proliferation, differentiation and survival during embryogenesis. To better visualize Isl1 expression and provide insight into the role of Isl1 during development, we generated an Isl1 nuclear LacZ (nLacZ) knockin mouse line and analyzed Isl1nlacZ expression during development by Xgal staining and compared expression of Isl1nlacZ with endogenous Isl1 by coimmunostaining with antibodies to Isl1 and β-galactosidase. Results demonstrated that during development Isl1 nuclear LacZ is expressed in a pattern that recapitulates its endogenous protein expression. Consistent with previous in situ and immunohistochemistry data, we observed Isl1nlacZ expression in multiple tissues and cell types, including the central and peripheral nervous system, neural retina, inner ear, pharyngeal mesoderm and endoderm and their derivatives (craniofacial structures, thymus, thyroid gland and trachea), cardiovascular system (cardiac outflow tract, carotid arteries, umbilical vessels, sinoatrial node and atrial septum), gastrointestinal system (oral epithelium, stomach, pancreas, mesentery) and hindlimb. In some cases, Isl1nlacZ appears to be more readily detectable than Isl1 protein when expression level is low, and in others, Isl1nlacZ appears to act as a lineage tracer, likely owing to perdurance of the nuclear localized beta-galactosidase.